2018
DOI: 10.1007/s11606-017-4303-8
|View full text |Cite
|
Sign up to set email alerts
|

Physician Perception of Pay Fairness and its Association with Work Satisfaction, Intent to Leave Practice, and Personal Health

Abstract: Physicians who thought their pay was fair reported greater work satisfaction, lower likelihood of leaving their practice, and better overall health. Addressing pay fairness perceptions may be important for sustaining a satisfied and healthy physician workforce, which is necessary to deliver high-quality care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 43 publications
4
40
1
Order By: Relevance
“… 53 A survey including 23 159 nurses from 10 European countries showed that 9% of all these nurses intended to leave their profession, varying from 5% to 17% among countries 54 Another survey performed among 2263 physicians in America reported that 18.4% of them intended to leave their practice. 55 A study conducted in Canada reported that 17.2% of registered nurses intended to leave their current nursing position. 17 Meanwhile, the prevalence of TI was lower than in some low-income and middle-income countries, such as Ghana, 20 Iraq, 56 South Africa 22 and the Philippines.…”
Section: Discussionmentioning
confidence: 99%
“… 53 A survey including 23 159 nurses from 10 European countries showed that 9% of all these nurses intended to leave their profession, varying from 5% to 17% among countries 54 Another survey performed among 2263 physicians in America reported that 18.4% of them intended to leave their practice. 55 A study conducted in Canada reported that 17.2% of registered nurses intended to leave their current nursing position. 17 Meanwhile, the prevalence of TI was lower than in some low-income and middle-income countries, such as Ghana, 20 Iraq, 56 South Africa 22 and the Philippines.…”
Section: Discussionmentioning
confidence: 99%
“…Like Herzberg et al (1959) in their dual-factor theory supposed, money does not create satisfaction but presence prevents dissatisfaction. A recent study reported that physicians pay satisfaction is associated with work satisfaction (Kao et al , 2018). In there, the authors concluded that pay fairness is important for a long-term cooperation and a basis to produce high-quality treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some types of compensation that are still high demand include base salary, merit pay and year-end bonus [8]. Issue of justice in providing rewards included in compensation is also the factor that determines employee job satisfaction [7,9] and improve expected outcomes [10].…”
Section: Introductionmentioning
confidence: 99%